Elaboration of the research method for milk dispersion in the jet slot type homogenizer - Samoichuk, Kyrylo; Самойчук, Кирило Олегович; Самойчук, Кирилл Олегович; Kovalov, Oleksandr; Ковальов, Олександр Олександрович; Ковалев, Александр Александрович; Oleksiienko, Vadym; Олексієнко, Вадим Олександрович; Алексеенко, Вадим Александрович; Palianychka, Nadiia; Паляничка, Надія Олександрівна; Паляничка, Надежда Александровна; et al. (My University, 2020)
The competitiveness improvement of milk products is directly connected with a problem of decreasing energy consumption of the process of milk emulsion dispersion. At creating promising types of energy effective dispersers, a necessary condition is to elaborate a correct methodology for studying them that takes into account the specificity of the process of fat milk microemulsion dispersion. Based on the critical analysis of research methods for homogenizers of different types, there have been determined main directions of their improvement, taken into account in the elaborated research method for a promising jet-slot type milk homogenizer. The method of theoretical studies, including a choice and analysis of stable and changeable factors of the homogenization process in a jet-slot type homogenizer and optimization criteria, has been elaborated. The interconnection of technological, constructive, hydraulic parameters with a dispersion quality has been demonstrated. The influence of physical-mechanical properties of milk as a research object was taken into account. An optimal milk temperature was chosen for the studies. Factor variation limits have been substantiated. The constructive scheme of a chamber for the experimental homogenizer has been developed. At processing the experimental research methodology, the main stage was to develop an experimental set for studying the influence of changeable factors of the dispersion process on a homogenization quality. Dispersion quality estimation methods have been analyzed and the method of microphotography has been chosen with further computed analysis of obtained data. The elaborated methodology was used at studying the influence of cream fat and ring slot width on a dispersion quality in a jet-slot type homogenizer. The obtained data allow to determine rational parameters of cream fat – 40–50 % and slot width – 0.1 mm. The analysis of dispersed characteristics of the milk emulsion allows to make a conclusion about the high homogenization quality, comparing with processing in a valve homogenizer.
Keywords: dispersion; milk homogenization; jet-slot type homogenizer; dispersion quality